Increasing the photocatalytic and fungicide activities of Ag3PO4 microcrystals under visible-light irradiation - Oliveira, Lucas Portela [UNESP]; Foggi, Camila Cristina de; Pimentel, Bruna Natália Alves da Silva [UNESP]; Assis, Marcelo; Andrés, Juan; Longo, Elson; Vergani, Carlos Eduardo [UNESP] (Elsevier, 2021)
The present study reports for the first time the performance of silver phosphate (Ag3PO4) microcrystals as photocatalyst (degradation of Rodamine B-RhB) and antifungal agent (against Candida albicans–C. albicans) under visible-light irradiation (455 nm). Ag3PO4 microcrystals were synthesized by a simple co-precipitation (CP) method at room temperature. The structural and electronic properties of the as-synthetized Ag3PO4 have been investigated before and after 4 cycles of RhB degradation under visible light using X-ray diffraction (XRD), micro-Raman spectroscopy, UV–Vis spectrophotometer and field emission scanning electron microscopy (FE-SEM) images. The antifungal activity was analyzed in planktonic cells and 48h-biofilm of C. albicans by colony forming units (CFU) counting, confocal laser and FE-SE microscopies. Statistical analysis was carried out using SPSS software. Morphological and structural modifications of Ag3PO4 were observed upon recycling. After 4 recycles, the material maintained its photodegradation property; an eightfold increase in the efficiency of Ag3PO4 was observed in planktonic cells and a two fold increase in biofilm when irradiated under visible light. Thus, higher antifungal effectiveness against C. albicans was obtained when associated with visible-light irradiation.
Keywords: Ag3PO4; Fungicide activity; Photocatalysis; Rhodamine B degradation; Visible light